Maintaining and disseminating the kilogram following its redefinition. (25th October 2017) - Stock, M; Davidson, S; Fang, H; Milton, M; de Mirandés, E; Richard, P; Sutton, C
Abstract: The new definition of the kilogram, which is expected to be adopted by the General Conference on Weights and Measures in 2018, will bring some major changes to mass metrology. The most fundamental change will be the replacement of the present artefact-based definition with a universal definition, enabling in principle any National Metrology Institute (NMI) to realize the kilogram. The principles for the realization and dissemination of the kilogram in the revised SI are described in the mise en pratique of the definition of the kilogram. This paper provides some additional information and explains how traceability can be obtained by NMIs that do not operate a primary experiment to realize the definition of the kilogram.